Above‐ and below‐ground herbivory effects on below‐ground plant–fungus interactions and plant–soil feedback responses. (22nd February 2013) - Martijn Bezemer, T.; van der, Wim H.; Martens, Henk; van de, Tess F. J.; Mulder, Patrick P. J.; Kostenko, Olga; Hutchings, Michael
Summary Feeding by insect herbivores can affect plant growth and the concentration of defense compounds in plant tissues. Since plants provide resources for soil organisms, herbivory can also influence the composition of the soil community via its effects on the plant. Soil organisms, in turn, are important for plant growth. We tested whether insect herbivores, via their effects on the soil microbial community, can influence plant‐soil feedbacks. We first examined the effects of above‐ground (AG) and below‐ground (B) insect herbivory on the composition of pyrrolizidine alkaloids (PAs) in roots and on soil fungi in roots and rhizosphere soil of ragwort (Jacobaea vulgaris). The composition of fungal communities in roots and rhizosphere soil was affected by both AG and BG herbivory, but fungal composition also differed considerably between roots and rhizosphere soil. The composition of PAs in roots was affected only by BG herbivory. Thirteen different fungal species were detected in roots and rhizosphere soil. The presence of the potentially pathogenic fungus Fusarium oxysporum decreased and that of Phoma exigua increased in presence of BG herbivory, but only in soil samples. We then grew new plants in the soils conditioned by plants exposed to the herbivore treatments and in unconditioned soil. A subset of the new plants was exposed to foliar insect herbivory. Plant‐soil feedback was strongly negative, but the feedback effect was least negative in soil conditioned by plants that had been exposed to BG herbivory. There was a negative direct effect of foliar herbivory on plant biomass during the feedback phase, but this effect was far less strong when the soil was conditioned by plants exposed to AG herbivory. AG herbivory during the conditioning phase also caused a soil feedback effect on the PA concentration in the foliage of ragwort. Synthesis. Our results illustrate how insect herbivory can affect interactions between plants and soil organisms, and via these effects how herbivory can alter the performance of late‐growing plants. Plant‐soil feedback is emerging as an important theme in ecology and these results highlight that plant‐soil feedback should be considered from a multitrophic AG and BG perspective.